2019
DOI: 10.1523/jneurosci.1308-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Exposing Pathological Sensory Predictions in Tinnitus Using Auditory Intensity Deviant Evoked Responses

Abstract: We tested the popular, unproven theory that tinnitus is caused by resetting of auditory predictions toward a persistent low-intensity sound. Electroencephalographic mismatch negativity responses, which quantify the violation of sensory predictions, to unattended tinnitus-like sounds were greater in response to upward than downward intensity deviants in 26 unselected chronic tinnitus subjects with normal to severely impaired hearing, and in 15 acute tinnitus subjects, but not in 26 hearing and age-matched contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 53 publications
1
40
0
2
Order By: Relevance
“…The assessment of both tinnitus and hyperacusis is essential in this population. However, some potential measurements for assessment may be off-limits due to their loud nature (e.g., (f)MRI, auditory brainstem responses, mismatch negativity or gap pre-pulse inhibition of startle response) [55][56][57]. The potential use of hearing aids to reduce the starkness of tinnitus may be restricted by the presence of hyperacusis.…”
Section: Implications For Diagnosis and Treatmentmentioning
confidence: 99%
“…The assessment of both tinnitus and hyperacusis is essential in this population. However, some potential measurements for assessment may be off-limits due to their loud nature (e.g., (f)MRI, auditory brainstem responses, mismatch negativity or gap pre-pulse inhibition of startle response) [55][56][57]. The potential use of hearing aids to reduce the starkness of tinnitus may be restricted by the presence of hyperacusis.…”
Section: Implications For Diagnosis and Treatmentmentioning
confidence: 99%
“…Emerging data suggest that tinnitus may be due to the breakdown of sensory gating circuitry between the auditory system and non-auditory limbic regions (Rauschecker et al, 2010;De Ridder et al, 2014), such that altered activity due to cochlear damage reaches the cortex and ultimately leads to a conscious percept (Rauschecker et al, 2010(Rauschecker et al, , 2015De Ridder et al, 2014). Specifically it has been suggested when the increased spontaneous activity in tinnitus patients fails to be ignored and is recognized as sound, this leads to a resetting of auditory predictions allowing the tinnitus to continue (Sedley et al, 2016(Sedley et al, , 2019. Debate does exist to the cause of the increased spontaneous activity as some suggest an increased neural gain (Sheppard et al, 2020) whereas others argue the increased neural gain is underlying hyperacusis but not tinnitus (Brotherton et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The reduced ABR amplitudes suggested a central pathology at the subcortical level. Sedley et al [2016Sedley et al [ , 2019 proposed an interesting theory of tinnitus causation. In this theory, those authors suggested that the origin of the tinnitus signal is spontaneous firing in the ascending auditory pathway that is usually successfully ignored as irrelevant noise.…”
Section: Discussionmentioning
confidence: 99%